STUDY ON THE CATEGORIES OF SPEECH FUNCTIONS USED IN DUNE FILM - Atika Aysara; M. Syarfi M. Syarfi; Masyhur Masyhur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: This study aims to examine the speech act functions found in the Dune film. To actualise this aims, this study was conducted using qualitative research designs and by making the speech act theory of (Levinson, 1979) and the speech act function theory of Searle (1979) as the basis for examining the speech act functions. The data were collected using the open coding and documentation method in which the oral data were collected from the utterances of the film, then transcribed into written data. This research used content or document analysis as the way to analyze the data. The data analysis result are presented informally or descriptively. The results of data analysis showed there are five speech act functions in the film, namely representative, directive, commissive, expressive, and declarative. The result finding shows that the speech function representative is at 57%, directive 20%, expressive 12%, declarative 7%, and commissive is at 4%. Examining the function and meaning of speech acts in the film Dune from the perspective of sociolinguistics is an important topic to raise as a method in language learning.Key Words: Function of Speech, Speech Act, Dune Film